(untitled) (International Journal of Engineering and Computer Science, 2017)
The widespread availability of wireless networks (Wi-Fi) has created an increased interest in harnessing them for other purposes, such as localizing mobile devices. While outdoor positioning has been well received by the public, its indoor counterpart has been mostly limited to private use due to its higher costs and complexity for setting up the proper environment. In this paper, we use local Wi-Fi network to localize a mobile user in an indoor environment.Wi-Fi (or 802.11 networking) works on the basic principal that data packets are sent using radio waves. These radio waves can be received by any compatible receiver placed in a pc, mobile phone, tablet pc or any other circuit. The aim of this research paper is to explore the application of 802.11 networking for localizing the user or the receiver by using RSSI i.e. Received signal strength indication. Through Wi-Fi, one may be able to track objects or people in real time,whilst adapting to changes in both the environment, and the Wi-Fi network, in a reliable manner. Since Distance and RSSI share a inverse relationship. RSSI can be used to locate the general location of the user. An experiment is conducted in order to view the relationship b/w RSSI and Distance in an indoor environment using some basic domestic based equipment and an android phone.